O atendimento à pessoa idosa em uma Unidade de Pronto Atendimento na percepção da equipe de enfermagem - Nascimento, Luís Gustavo Delboni (2022)
Introduction: The elderly person presents characteristics resulting from the aging process that differ from people of other age groups regarding the presentation, onset and outcome of health problems. To fully assist these people, health services must develop mechanisms to improve the work process. This study seeks to meet an institutional demand for improvements in the care of the elderly, which instigated the development of an educational video. Objective: To identificate elderly patient care in an Emergency Care Unit based on the nursing team's perception. Developing an educational technology on elderly care as an intervention strategy. Method: Qualitative study of exploratory, descriptive and field type, with 20 nursing professionals of an Emergency Care Unit of the Metropolitan Region of Grande Vitória - Espírito Santo. Data production took place through semi-structured interviews, analyzed through content analysis. Results: The data analysis revealed the following categories: (1) identifying the reflections of the Municipal Health Network Management in the care of the elderly in an urgency and emergency unit; (2) identifying the influences on urgency and emergency care to the elderly; (3) contextualizing the care of the elderly in the urgency and emergency service; (4) Unveiling the elderly in the light of health professionals of an urgency and emergency unit. Products: Based on the categories that emerged from the data collected and that were based on Bardin's content analysis, this dissertation generated as products a) the development of 04 educational scripts for the construction of a series of educational videos on the care of the elderly person, aimed at health professionals b) an educational video on the care of the elderly person, c) a brand named "CONECTA GERONTO", d) two characters -Dona Rosa and nurse Aline-, e) 1 scientific article and f) 01 educational poster on the care of the elderly person. Considerations: The present research allowed to evaluate how the care to the elderly person is being developed in the institution, and this information subsidized the development of the product. This research has the potential to have an impact on the reality of the service through the results found, and through the products developed. This research is expected to subsidize discussions and reflections on the care of the elderly in emergency services, stimulating the development of strategies for intervention and change of reality.